The association between polymorphisms in tankyrase gene and telomere length in omethoate–exposed workers. (January 2020) - Yang, Yongli; Tan, Jiebing; Duan, Xiaoran; Zhang, Hui; Feng, Xiaolei; Wang, Tuanwei; Wang, Pengpeng; Ding, Mingcui; Liu, Suxiang; Li, Lei; Liang, Haiyong; Yao, Wu; et al.
Abstract: Peripheral blood leukocyte telomere length in omethoate–exposed workers is related to environmental exposure and single nucleotide polymorphisms (SNPs) in genes including p21, GSTM1, miR-145, etc. However, the roles of SNPs in tankyrase ( TNKS ) gene in telomere length are still unknown. The aim of this study was to explore the association between SNPs in TNKS gene and telomere length in omethoate–exposed workers. Telomere length in peripheral blood leukocyte DNA from 180 omethoate-exposed workers and 115 healthy controls was measured using Real-time quantitative polymerase chain reaction (PCR). Genotyping of the selected functional and susceptible SNPs was performed by the flight mass spectrometry based on PCR and single-base extension. The analysis of covariance was performed to find effects of SNPs on telomere length. Generalized linear models were used to analyze the environment, gene, and interaction on telomere length. The results showed that telomere length in the CG + CC genotypes in rs1055328 in TNKS gene was significantly longer than that in the wild homozygous GG genotype both in exposure group ( P = 0.017) and in control group ( P = 0.038) after adjusting the covariates. The variables kept in the generalized linear models included omethoate-exposure ( β = 0.580, P = 0.001) and rs1055328 (CG + CC) in TNKS gene ( β = 0.339, P = 0.002). The study suggests that the prolongation of telomere length is associated with omethoate-exposure and the CG + CC genotypes in rs1055328 in TNKS gene. Highlights: A new method is established for detecting seven SNPs in TNKS gene by MALDI-TOF MS. Omethoate workers carrying rs1055328 CG + CC genotypes have longer telomere. Other six SNPs are unrelated to changes in telomere length in omethoate workers.